STATUS PERKEMBANGAN DAN IDENTITAS DIRI REMAJA DI SMP NEGERI 49 KRAMAT JATI JAKARTA TIMUR - Harizza Pertiwi; Zakiyah; Aan Sutandi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Adolescence is a period of change in biological, psychological, and social aspects from childhood toadulthood. At this range of time, these changes can affect the development process and identityformation. This process may start at the early stage of adolescence which is in the age of junior highschool. If adolescent developmental and identity status are not robust, adolescents tend to be easilyexposed to negative behavior such as drug abuse and free sex. The purpose of this study was todetermine the status of development and identity of adolescents in SMP Negeri 49 East Jakarta. Themethod used was descriptive quantitative to describe or to give illustration of the object beingstudied. Number of respondents was 21 adolescence which attained by calculation using purposivesampling technique. The results obtained are that most respondents have achieved optimaldevelopment (85,7%) and more than half of respondents have active identity (57,1%). From theseresults, it can be seen that not all respondents have achieved optimal development, and there arestill many whose identities are less active. This is a natural phenomenon since the development andidentity are still in process throughout adolescence until the age of eighteen. Furthermore, it can beconcluded that the optimization of development achievement and adolescent self-identity is stillneeded, for this reason, efforts to promote adolescent health can be carried out both in schools andin the community setting.